2021
DOI: 10.1101/2021.07.10.451626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-invasive imaging of tau-targeted probe uptake by whole brain multi-spectral optoacoustic tomography

Abstract: AimAbnormal tau accumulation plays an important role in tauopathy diseases such as Alzheimer’s disease and Frontotemporal dementia. There is a need for high-resolution imaging of tau deposits at the whole brain scale in animal models. Here, we demonstrate non-invasive whole brain imaging of tau-targeted PBB5 probe in P301L model of 4-repeat tau at 130 μm resolution using volumetric multi-spectral optoacoustic tomography (vMSOT).MethodsThe binding properties of PBB5 to 4-repeat K18 tau and Aβ42 fibrils were ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Animal models, such as P301L and P301S, that recapitulate pathological features of 4R tauopathy have been developed with mutations in the MAPT gene, ( Lewis et al, 2000 ; Gotz et al, 2001 ; SantaCruz et al, 2005 ; Spires et al, 2006 ), as well as hTau and knock in animal models ( Saito et al, 2019 ; Hosokawa et al, 2021 ). The in vivo imaging of tau has been demonstrated in animal models using [ 18 F]APN-1607, [ 11 C]PBB3, [ 11 C]mPBB5, [ 18 F]THK5117, and [ 18 F]JNJ64349311 ( Maruyama et al, 2013 ; Brendel et al, 2016 , 2018 ; Declercq et al, 2017 ; Ishikawa et al, 2018 ; Ni et al, 2018 ; Tagai et al, 2020 ; Vagenknecht et al, 2021 ), as well as SPECT using [ 123 I]PIP-NHMe ( Watanabe et al, 2021 ). It is noted that [ 18 F]flortaucipir did not detect tau in the rTg4510 (P301L) 4R-tau mouse model ( Marquié et al, 2015 ; Ni et al, 2018 ).…”
Section: Positron Emission Tomography For Proteinopathies In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Animal models, such as P301L and P301S, that recapitulate pathological features of 4R tauopathy have been developed with mutations in the MAPT gene, ( Lewis et al, 2000 ; Gotz et al, 2001 ; SantaCruz et al, 2005 ; Spires et al, 2006 ), as well as hTau and knock in animal models ( Saito et al, 2019 ; Hosokawa et al, 2021 ). The in vivo imaging of tau has been demonstrated in animal models using [ 18 F]APN-1607, [ 11 C]PBB3, [ 11 C]mPBB5, [ 18 F]THK5117, and [ 18 F]JNJ64349311 ( Maruyama et al, 2013 ; Brendel et al, 2016 , 2018 ; Declercq et al, 2017 ; Ishikawa et al, 2018 ; Ni et al, 2018 ; Tagai et al, 2020 ; Vagenknecht et al, 2021 ), as well as SPECT using [ 123 I]PIP-NHMe ( Watanabe et al, 2021 ). It is noted that [ 18 F]flortaucipir did not detect tau in the rTg4510 (P301L) 4R-tau mouse model ( Marquié et al, 2015 ; Ni et al, 2018 ).…”
Section: Positron Emission Tomography For Proteinopathies In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Positron emission tomography (PET) imaging of tau in tauopathy mouse models using various tau-targeted radioligands has been established ( Maruyama et al, 2013 ; Brendel et al, 2016 ; Ono et al, 2017 ; Ishikawa et al, 2018 ; Ni et al, 2018 ; Tagai et al, 2020 ; Chaney et al, 2021 ; Cao et al, 2022 ). In addition, fluorescence imaging, two-photon microscopy, and photoacoustic imaging methods have been developed for in vivo mapping of tau accumulation in animal models ( Wu et al, 2018 ; Calvo-Rodriguez et al, 2019 ; Ni et al, 2020a ; Vagenknecht et al, 2021 ). To date, a few MRI tau imaging studies have been reported assisted with contrast agents ( Table 1 ).…”
Section: Tau Imagingmentioning
confidence: 99%
“…OA microscopy with Congo red has been used for the detection of amyloid-β plaques and cerebral amyloid angiopathy in the APP/PS1 mouse model (Hu et al, 2009;Zhou et al, 2021). OA tomography with chemical dye PBB5 (PBB3 derivative) for detection of β-sheet-containing tau deposits in the P301L 4-repeat tau mouse model has been reported (Ono et al, 2017;Vagenknecht et al, 2021). It is foreseeable that OA tomography pipeline with the deep brain region detection capability will be applied together with OA/fluorescence β-sheet-binding dyes to image other proteiopathy disease models, such as Parkinson's disease mouse model with α-synuclein accumulation and the amyotrophic lateral sclerosis animal model with TAR DNA-binding protein 43 deposits.…”
Section: Chemical Dyesmentioning
confidence: 99%